CRITICAL REVIEW ON IMPACT OF ARTIFICIAL INTELLIGENCE ON MARKETING (International Journal of Food and Nutritional Sciences, 2022)
Marketing strategies may benefit from AI's enhancements, and the technology can also be used to generate and distribute value to consumers in novel ways. For instance, by incorporating AI into social media marketing and programmatic advertising, a more complete picture of predictive analytics, consumer behaviour, and deeper insights may be achieved. Biometrics, speech, and conversational user interfaces are just a few examples of the innovative new marketing techniques that may benefit both businesses and customers. All of these developments have the traits of hyper-personalization, cost-effectiveness, scalability, and in-depth comprehension.